Supra-organization and optical anisotropies of the extracellular matrix in the amniotic membrane and limbal stroma before and after explant culture - Valdetaro, Gisele P. [UNESP]; Aldrovani, Marcela [UNESP]; Padua, Ivan R. M. [UNESP]; Cristovam, Priscila C.; Gomes, Josï¿½ A. P.; Laus, Josï¿½ L. [UNESP] (My University, 2016)
In this research we evaluated the supramolecular organizations and the optical anisotropical properties of the de-epithelialized human amniotic membrane and rabbit limbal stroma, before and after explant culture. Birefringence, monochromatic light spectral absorption and linear dichroism of the main extracellular matrix biopolymers, that is, the fibrillar collagens and proteoglycans, were investigated by polarized light microscopy combined with image analysis. Our results demonstrated that the culture procedure–induced stimuli altered the supra-organizational characteristics (in terms of collagens/proteoglycans spatial orientation and ordered-aggregational state) of the amniotic and limbal extracellular matrix, which led to changes in optical anisotropical properties.
Keywords: Anisotropic optical materials; Biology and medicine; Birefringence; Dichroism; Ophthalmology; Polarization